Analysis of Factors Influencing Interest in Accounting Students in Taking Accounting Certification: Analisis Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi dalam Pengambilan Sertifikasi Akuntansi - Wulansari, Srifany; Hariyanto, Wiwit (Indonesian Journal of Innovation Studies, 2023)
The quality of resources greatly affects the development of the country’s economy. One way that is done by the community to increase their quality is by taking education in college. The economics major that many people choose is the accounting major. Due to the large number of accounting graduates, accountants compete with each other by taking accounting certifications. However, there are still many students who do not know the importance of taking accounting certification. The importance of accounting certification for accounting students should make accounting students to take accounting certification. However, there are still many accounting students who underestimate the importance of accounting certification. This study aims to determine whether factors such as understanding, economy, quality, and career can affect the interst of accounting students in taking accounting certification. The object used in this research is the 2018 class of accounting students at the Muhammadiyah University of Sidoarjo. The sample used is 73 respondents using simple random sampling method. The data analysis used is multiple regression analysis using SPSS version 26 application. The result of this study show that only understanding effects the interest of accounting students in taking accounting certification. Meanwhile, economy, quality, and career have no effect on the interest of accounting students in taking accounting certification.